Spreadsheet Implementation for Optimization of Power flow Network Problem: A Case Study of Kathmandu Valley - Acharya, Sujan; Tewari, Anand (SCITECH Nepal, 2019)
This paper is about the optimization of power loss in the power transmission network of the Kathmandu valley using spreadsheet modeling as an optimal power flow software. It is helpful for identifying the best path for the optimum power flow in dry as well as wet season. The available generating stations and substations taken as supply and demand nodes near Kathmandu valley are considered and the network is optimized as a transshipment flow problem. The main goal in this network flow model is to determine how much power should be allowed to flow across each transmission lines with minimal losses. In addition, optimization is performed considering the power import from India as well. Considering active power flow with a different scenario, and depending upon the load demand, the power system network is modeled in order to find out the best possible routes for efficient power flow with minimum loss.